Integration of AI-Powered Chatbots in Nursing Education: A Scoping Review of Their Utilization, Outcomes, and Challenges - Labrague, Leodoro J.; Sabei, Sulaiman Al (Teaching and learning in nursing, 2025)
•Artificial Intelligence (AI)-based platforms, including chatbots, are increasingly utilized in higher education, particularly in nursing education.•AI-based chatbots have significant potential to enhance student engagement, improve knowledge retention, and support skill development.•Nursing education programs should consider integrating chatbots as a complementary pedagogical tool; however, caution is warranted due to the ongoing refinement of these technologies. Chatbots powered by artificial intelligence (AI) have revolutionized teaching methodologies, especially in education. In nursing education, these AI-driven chatbots present substantial potential for enhancing student learning, engagement, and educational processes. This scoping review aimed to synthesize existing literature on the use of AI-powered chatbots as teaching tools in nursing education, evaluating their effectiveness. This is a scoping review guided by the five-stage scoping review protocol of Arksey and O'Malley (2005). A systematic search and retrieval of relevant articles was conducted across CINAHL, PubMed, Web of Science, Scopus, and Eric databases. Deductive content analysis based on the methodology of Elo and Kyngäs (2008) was used for a narrative synthesis of the findings. A total of 14 studies were included in this review. ChatGPT emerged as the predominant platform for deploying chatbots within nursing education. The primary applications of chatbots were identified as follows: (a) enhancing learning and skill development, (b) supporting simulations, (c) providing educational assistance and tutoring, and (d) facilitating evaluation and assessment. Significant outcomes reported included increased knowledge retention, heightened engagement, and improved skill development among nursing students. The integration of chatbots in nursing education has proven to be a valuable tool for improving student learning outcomes, engagement, and skill development, while also offering effective feedback and evaluation mechanisms. Nurse faculty might consider integrating chatbots to complement traditional teaching methods, but it is essential to continue rigorous research and refinement of the technology, alongside comprehensive educator training, to effectively address existing limitations and challenges.